The dangers of modern means of communication on the value system of Anbar University students from their teaching point of view (Journal of the College of Basic Education, 2022)
The current research aims to identify (the dangers of modern means of communication on the system of values ​​among the students of the University of Anbar from the point of view of their teachers, and to achieve the goal of the research, the question is what is the extent of the dangers of communication on the system of values ​​among the university students, and to answer it, the research sample included the teachers of the University of Anbar, whose number is (765) distributed among (20) faculties, and the researcher adopted 15% of them as a sample for the research, and it reached (115) teachers for the academic year (2016-2017). And the percentage weight of the paragraphs, and after showing the results and their interpretation, the researcher made several recommendations, and then suggested valid proposals for research.